Estudio de factibilidad para la creación de una empresa de asesoramiento financiero para micros empresarios cantón Buena Fe, año 2015 - Zamora Pérez, Ingrid Stefania (2016)
This research paper called Feasibility Study is intended to provide financial advisory services to micro entrepreneurs Canton Good Faith, the development of this project seeks to meet the existing needs of the service. For this reason the initiative to undertake a significant investment that allows running this project was. In developing this work research methods helped collect, sort, and classify information necessary to carry out this project were applied. Research conducted by the market research showed that there is a need for the service you want to provide. Thus being able to observe through the results that the project will run well received. The technical study on the project demonstrated an investment in the first year of 21,000 with incomes that are justified with a value of 37,500 and an acceptance of 85% according to the economically active population of the corner which corresponds to 15,684 indicating that the project is economically feasible according to the technical study performed. To find the weaknesses and threats strength of the company was necessary to apply the SWOT analysis evaluating the competitive environment by providing a quality service to customers and to meet the objectives of the company. Financial economic evaluation applied to the project has shown that high levels of profitability finding a van which is located at 29.533.95 indicating that the project is financially feasible, the IRR stood at 96% at a cost of 1.95 profit making the project to be profitable in the medium term.